2010
DOI: 10.1007/s00216-010-4460-7
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopy to study degradation of natural dyes. Assessment of oxygen-free cassette for safe exposition of artefacts

Abstract: An important issue connected with conservation chemistry is how to improve the storage and exposure conditions in order to suppress the fading and degradation of dyes and other components of paintings. Although the oxygen-free exposure cassettes are commonly known in museums, there is still lack of information in the literature about the effect of anoxic conditions on the degradation of dyes. This study is an attempt to start a database formation on the dyes degradation. Five commercial dyes (indigo, dragon's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 21 publications
3
30
0
2
Order By: Relevance
“…, possibly due to OH groups vibrations [20]; at 2096 cm -1 is a non-identified band; at 1632 cm -1 , it could be related to stretching vibration of aromatic C=C; a "shoulder" at 1526 cm -1 was not identified; at 1450 cm -1 could be due to stretching vibration of aromatic C=C; at 1340 cm -1 could be related to rocking vibration of aromatic CH; at 1291 cm -1 was not identified; at 1209 cm -1 would be due to the stretching vibration of (O-CH3); the band at 1149 cm -1 was not identified; the band at 1080 cm -1 could possibly be related to the stretching vibration of (C-O-C) [30]. The band at 1045 cm -1 was not identified.…”
Section: Discussionmentioning
confidence: 97%
“…, possibly due to OH groups vibrations [20]; at 2096 cm -1 is a non-identified band; at 1632 cm -1 , it could be related to stretching vibration of aromatic C=C; a "shoulder" at 1526 cm -1 was not identified; at 1450 cm -1 could be due to stretching vibration of aromatic C=C; at 1340 cm -1 could be related to rocking vibration of aromatic CH; at 1291 cm -1 was not identified; at 1209 cm -1 would be due to the stretching vibration of (O-CH3); the band at 1149 cm -1 was not identified; the band at 1080 cm -1 could possibly be related to the stretching vibration of (C-O-C) [30]. The band at 1045 cm -1 was not identified.…”
Section: Discussionmentioning
confidence: 97%
“…As expected, characteristic signals generally attributed to the lake pigment were identified (Figure 8a): bands for the hydroxyl stretching (νOH) at 3400 cm −1 , carbonyl groups (νC=O, 1645 cm −1 ), aromatic rings (νC=C, 1530 cm −1 ) and aliphatic chains (δC-H 2 , 1425 cm −1 ), as well as the strong peak of sulfates (νS-O, at 1105 cm −1 ) are clearly identifiable [34,35]. As shown in Figure 8a, the aged ML (t = 520 h) shows a strong increase of the band at 1645 cm −1 , probably due to the presence of degradation products such as benzoic acid, phthalic anhydride and dimethyl phthalate [36].…”
Section: Suggested Assignmentmentioning
confidence: 99%
“…Changes in the vibrational spectra suggest that anthraquinones undergo aromatic ring opening and that adsorbed water on the sample can enhance the degradation [14]. Examination of the decolorization mechanism of dyeing effluent by a fungus has provided some insight into the degradation process, showing the fungus degrades the carminic acid via a two-step process of glucose cleavage followed by a ring cleavage reactions [17].…”
Section: A N U S C R I P Tmentioning
confidence: 98%
“…A study of the stability of the dry pigment, monitored using vibrational spectroscopy, indicated enhanced photodegradation under anoxic conditions [14]. In contrast, anoxic conditions were found to stabilize or slow the photo-induced degradation of carmine lake in paint samples [6,7,15].…”
Section: A N U S C R I P Tmentioning
confidence: 98%